Beauty is in the eye of the employer: Labor market discrimination of accountants - Shapir, Offer Moshe; Shtudiner, Zeev (Frontiers in Psychology, 2022)
This research investigates labor market discrimination based on physical appearance in Israel’s Certified Public Accountant firms. Using a survey questionnaire, we showed that accountants in managerial positions prefer to hire more physically attractive candidates. This beauty premium is larger among the five biggest Certified Public Accountant firms and can be explained by the perception that attractive candidates possess essential traits for becoming successful accountants. An important implication of our results is that even among accounting firms, where professionalism is well defined, discrimination against candidates based on traits such as physical appearance can ineffectively eliminate suitably qualified interns.